Reactive Arthritis Triggered by Adalimumab and Leflunomide in a Patient with Ankylosing Spondylitis - Liu Y; He J; Jiang J; Wang Y; Liu T (Dove Medical Press, 2022)
Ying Liu, Jia He, Jingjing Jiang, Yujuan Wang, Ting Liu Department of Dermatology, Affiliated Hospital of North Sichuan Medical College, Nanchong, People's Republic of ChinaCorrespondence: Ting Liu, Department of Dermatology, Affiliated Hospital of North Sichuan Medical College, No. 1 Maoyuan South Road, Shunqing District, Nanchong, Sichuan Province, 637000, People's Republic of China, Tel +8615082780013, Email 332656467@qq.comAbstract: Reactive arthritis (ReA) is uncommon. The present case is a Chinese man who has been treated with adalimumab and leflunomide to control ankylosing spondylitis (AS). During the treatment, the patient developed a range of symptoms, including fever, fatigue, pustular rash, suppurative urethritis, genital ulcers, oral ulcers, bilateral uveitis, heel pain and swelling and pain of the knee and ankle joints. The laboratory studies revealed the presence of HLA-B27, and urethral secretions were positive for Ureaplasma urealyticum. The patient was eventually diagnosed with ReA. The development of ReA may be related to the combination of adalimumab and leflunomide, which reduces immune function and triggers activation of potential U. urealyticum. The patient received 3 weeks of antibiotics, corticosteroids and non-steroidal anti-inflammatory drugs (NSAIDs), resulting in a significant improvement. The dose of corticosteroids was gradually reduced, and adalimumab was reintroduced. The patient was followed up for 3 months without recurrence.Keywords: reactive arthritis, Reiter syndrome, ankylosing spondylitis, urethritis, arthritis, uveitis, HLA-B27